Iron status of malaria and control subjects attending selected hospital in Sokoto Metropolis, Nigeria - A.I. Umar; Yusuf Sarkingobir; AI Umar; AM Labbo; M Almustapha; Ummu Tukur (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The association of nutritional status and malarial disease is complex with multiple dimensions. Deficiencies in some of these nutritional parameters rethought to lead to malnutrition with subsequent susceptibility to malaria infection. The objective of this study is to determine iron status of malaria and control subjects attending selected hospitals in Sokoto metropolis, Nigeria. Serum iron was measured by the method of Nitro-PAPS. TBC was assessed calorimetrically while Transferrin and UIBC were determining using specific sharing formula. Result of the study observed significant(p<0.005) increased in TIBC level of most male infected individuals compared to female infected whereas a decreased in Transferrin level in about all male infected individuals than in female infected and vice-visa. The serum iron levels are comparatively low due to redistribution of iron from the serum into the tissue storage forms (transferrin). Also, the percentage transferrin is low, perhaps due to the body absorbing more transferrin than needed, inadequate production of transferrin by the liver which is the major site of malaria infection or excess excretion of transferrin in the urine by the kidneys. After a general analysis, the study observed that serum iron, TIBC and transferrin are highly affected by the malaria.